Pengaruh Foto Produk, Online Customer Review dan Online Customer Rating Terhadap Minat Beli Di E-commerce Tiktok Shop (Studi Kasus Pada Mahasiswa FEB Unisma Angkatan 2019) - Fatmawati, Yenni Diah; Mardani, Ronny Malavia; Arsyianto, M. Tody (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research was carried out with the aim of finding out and analyzing the influence of product photos, online customer reviews and online customer ratings on buying interest in the e-commerce Tiktok Shop with a case study of students from the Faculty of Economics and Business at Unisma class of 2019. The samples in this research used purposive sampling and explanatory research with a quantitative approach. The sample in this study was 90 respondents. Data collection techniques by distributing questionnaires. The data analysis method uses multiple linear regression analysis, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, hypothesis test and coefficient of determination. The analysis tool used is IBM SPSS 26. Based on the research results, it is known that partially product photos have a positive and significant influence on purchase interest, online customer reviews have a positive and significant influence on purchase interest, and online customer ratings have a positive and significant influence on purchase interest. Keywords: Product Photos, Online Customer Reviews, Online Customer Ratings, Purchase Interest